2018
DOI: 10.1007/s12519-017-0115-5
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequality in screen time frequency in children and adolescents: the weight disorders survey of the CASPIAN IV study

Abstract: Socioeconomic inequality in ST frequency was in favor of low SES groups. These findings are useful for health policies, better programming and future complementary analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…In a similar study conducted in 2015 by Moradi et al In Sanandaj, 50% of boys and 45% of girls had an average of more than 2 hours of Screen Time activity per day (21). In other similar studies, the reported values are lower than the present study (22)(23)(24), this can be due to the effects of time and the tendency of adolescents to use televisions, computers, and various methods of using them. In most studies comparing Screen Time activity between girls and boys, same as the results of our study, a higher proportion of this activity was reported in boys (24,25); in some of them, the differences were statistically signi cant (21,22,26).…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…In a similar study conducted in 2015 by Moradi et al In Sanandaj, 50% of boys and 45% of girls had an average of more than 2 hours of Screen Time activity per day (21). In other similar studies, the reported values are lower than the present study (22)(23)(24), this can be due to the effects of time and the tendency of adolescents to use televisions, computers, and various methods of using them. In most studies comparing Screen Time activity between girls and boys, same as the results of our study, a higher proportion of this activity was reported in boys (24,25); in some of them, the differences were statistically signi cant (21,22,26).…”
Section: Resultscontrasting
confidence: 84%
“…There is no clear association between phone use and screen time with socioeconomic status. Recent studies show that screen time activities, owning mobile phone, and phone use is much more in children with lower socioeconomic status than high (SES) (8,9), but another study showed an utterly different result that owning a phone and phone use is higher in teenage children with higher socioeconomic status families (10).…”
mentioning
confidence: 99%
“…However, this trend is not (yet) generalizable all over the world. For example, a recent study found that in Iran, individuals with higher SES had a significantly higher risk of prolonged ST, watching TV, and working with computers (Heshmat et al, 2018). Earlier studies show that this is similar to the behavior in western countries during the early 2000s (Vandelanotte, Sugiyama, Gardiner, & Owen, 2009).…”
Section: Discussionmentioning
confidence: 84%
“…These circumstances were summarized before in a meta-analysis by Mielke, Brown, Nunes, Silva, and Hallal (2017) which found that the direction of the association between SES and sedentary behaviors varies between high-income and low-to middle-income countries. Besides that, the majority of studies with data from the early to mid-2010s and before found that girls have a decreased risk of prolonged ST compared to boys (Heshmat et al, 2018;Sigmundová et al, 2017;Saunders & Vallance, 2017). However, this trend has to be questioned with recent data as more and more studies find similar ST among girls and boys, most likely explained by an increase in the use of social networking platforms by girls (Hinkley, Brown, Carson, & Teychenne, 2018;Simón-Montañes, Solana, García-Gonzalez, Catalán, & Sevil-Serrano, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Disentangling and quantifying the relative importance of each of those characteristics on educational disparities in smoking among adolescents can provide insights to design tailored interventions aimed at reducing these disparities. The Oaxaca-Blinder decomposition method [15,16] is a statistical tool adapted for this purpose, and has commonly been used to study sources of disparities in health, including smoking behaviours [17][18][19] and adolescent health [20,21], but has not yet been applied to educational disparities in smoking among adolescents. The Oaxaca-Blinder decomposition method decomposes a given disparity between 2 groups into a portion due to a statistical variation in the covariates of interest (the explained portion) and an unexplained portion (that includes the effect of unmeasured variables) [22].…”
mentioning
confidence: 99%